2018
DOI: 10.1590/01047760201824042605
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Atlantic Forest Trees and Their Influence on Topsoil Fertility in the Southeastern Brazil

Abstract: All evaluated tree species showed growth increases up to 21 years. The evaluated trees have potential for recovery degraded areas. The edaphic system was able to become self-sustainable under all tree stands. The evaluated trees changed the topsoil fertility differentially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…Given the uniqueness of these common gardens, they should not be neglected. Yet, differences in the topsoil properties among species located at the same study site were previously described by Barroso et al (2018) also through con dence intervals which validates our analysis.…”
Section: Soil Sampling and Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…Given the uniqueness of these common gardens, they should not be neglected. Yet, differences in the topsoil properties among species located at the same study site were previously described by Barroso et al (2018) also through con dence intervals which validates our analysis.…”
Section: Soil Sampling and Analysissupporting
confidence: 89%
“…Gaseous N losses frequently happen in N-saturated tropical systems due to soil capacity limitations (Bingham and Cotrufo 2016) (Callesen et al 2013). Yet, nitri cation in soils could reduce soil pH by producing protons in its chemical processes (Wang et al 2010) and the lowest pH was observed for P. reticulata (Barroso et al 2018), and both facts support our previous assumption.…”
Section: Soil 13 C and 15 N Abundance Uctuationssupporting
confidence: 82%
See 3 more Smart Citations